Enhanced climate resilience in agriculture: Entry points for public action in Kenya - Ringler, Claudia; Woelcke, Johannes; Okoba, Barrack; Bryan, Elizabeth (International Food Policy Research Institute, 2011)
Climate is a robust determinant of both agricultural and general economic performance in Kenya and elsewhere in rainfed Sub-Saharan Africa. Frequent droughts and floods have cost the Kenyan economy billions of Ksh, and adverse impacts and costs are expected to rise over time. Drought is by far the most pressing climate-related shock experienced by Kenyan farmers, resulting in declines in crop yields, food shortages, and food price spikes. At the same time, climate change is expected to result in a drier coast while the highlands and northern Kenya are likely to become wetter. However, increases in rainfall in lowland areas may not lead to increases in agricultural productivity since increases in temperature will also increase evapotranspiration, offsetting any potential increase in productivity; and increases in precipitation elsewhere will be too low to support a growing season. What can the Kenyan Government, the private sector, and community-based organizations do to increase resilience to current and future adverse impacts from climate change?